Visual examination and dermoscopy, alone or in combination, for the diagnosis of keratinocyte skin cancers in adults - Dinnes, Jacqueline; Deeks, Jonathan J.; Chuchu, Naomi; Matin, Rubeta N.; Wong, Kai Yuen; Aldridge, Roger Benjamin; Durack, Alana; Gulati, Abha; Chan, Sue Ann; Johnston, Louise; Bayliss, Susan E.; Leonardi-Bee, Jo; et al. (Wiley, 2018)
Background Early accurate detection of all skin cancer types is important to guide appropriate management, to reduce morbidity and to improve survival. Basal cell carcinoma (BCC) is almost always a localised skin cancer with potential to infiltrate and damage surrounding tissue, whereas a minority of squamous cell carcinoma (cSCC) and invasive melanoma are higher risk skin cancers with the potential to metastasise and cause death. Dermoscopy has become an important tool to assist specialist clinicians in the diagnosis of melanoma, and is increasingly used in primary care settings. Dermoscopy is a precision-built handheld illuminated magnifier that allows more detailed examination of the skin down to the level of the superficial dermis. Establishing the value of dermoscopy over and above visual inspection for the diagnosis of BCC or cSCC in primary and secondary care settings is critical to understanding its potential contribution to appropriate skin cancer triage, including referral of higher risk cancers to secondary care, the identification of low risk skin cancers that might be treated in primary care and to provide reassurance to those with benign skin lesions who can be safely discharged. Objectives To determine the diagnostic accuracy of visual inspection and dermoscopy, alone or in combination, for the detection of a) BCC and b) cSCC, in adults. Studies were separated according to whether the diagnosis was recorded face-to-face (in-person) or based on remote (image-based) assessment. Search methods We undertook a comprehensive search of the following databases from inception up to August 2016: Cochrane Central Register of Controlled Trials; MEDLINE; Embase; CINAHL; CPCI; Zetoc; Science Citation Index; US National Institutes of Health Ongoing Trials Register; NIHR Clinical Research Network Portfolio Database; and the World Health Organization International Clinical Trials Registry Platform. We studied reference lists and published systematic review articles. Selection criteria Studies of any design that evaluated visual inspection and/or dermoscopy in adults with lesions suspicious for skin cancer, compared with a reference standard of either histological confirmation or clinical follow-up. Data collection and analysis Two review authors independently extracted all data using a standardised data extraction and quality assessment form (based on QUADAS-2). We contacted authors of included studies where information related to the target condition or diagnostic threshold were missing. We estimated accuracy using hierarchical summary ROC methods. Analysis of studies allowing direct comparison between tests was undertaken. To facilitate interpretation of results, we computed values of sensitivity at the point on the SROC curve with 80% fixed specificity and values of specificity with 80% fixed sensitivity. We investigated the impact of in-person test interpretation; use of a purposely developed algorithm to assist diagnosis; and observer expertise. Main results A total of 24 publications reporting on 24 study cohorts were included, providing 27 visual inspection datasets (8805 lesions; 2579 malignancies) and 33 dermoscopy datasets (6855 lesions; 1444 malignancies). The risk of bias was mainly low for the index test (for dermoscopy evaluations) and reference standard domains, particularly for in-person evaluations, and high or unclear for participant selection, application of the index test for visual inspection and for participant flow and timing. Concerns regarding the applicability of study findings were scored as ‘high’ or 'unclear' concern for almost all studies across all domains assessed. Selective participant recruitment, lack of reproducibility of diagnostic thresholds and lack of detail on observer expertise were particularly problematic. The detection of BCC was reported in 28 datasets; 15 on an in-person basis and 13 image-based. Analysis of studies by prior testing of participants and according to observer expertise was not possible due to lack of data. Studies were primarily conducted in participants referred for specialist assessment of lesions with available histological classification. No clear differences in accuracy were noted between dermoscopy studies undertaken in-person and those which evaluated images. The lack of effect observed is likely due to other sources of heterogeneity, including variations in the types of skin lesion studied, in dermatoscopes used, in the use of algorithms and varying thresholds for deciding on a positive test result. Meta-analysis found in-person evaluations of dermoscopy (7 evaluations; 4683 lesions and 363 BCCs) to be more accurate than visual inspection alone for the detection of BCC (8 evaluations; 7017 lesions and 1586 BCCs), with an RDOR of 8.2 (95% CI: 3.5 to 19.3; P < 0.001). This corresponds to predicted differences in sensitivity of 14% (93% vs 79%) at a fixed specificity of 80% and predicted differences in specificity of 22% (99% vs 77%) at a fixed sensitivity of 80%. Very similar results were observed for the image-based evaluations. When applied to a hypothetical population of 1000 lesions, of which 170 are BCC (based on median BCC prevalence across studies), an increased sensitivity of 14% from dermoscopy would lead to 24 fewer BCCs missed, assuming 166 false positive results from both tests. A 22% increase in specificity from dermoscopy with sensitivity fixed at 80% would result in 183 fewer unnecessary excisions assuming 34 BCCs missed for both tests. There was not enough evidence to assess the use of algorithms or structured checklists for either visual inspection or dermoscopy. Insufficient data were available to draw conclusions on the accuracy of either test for the detection of cSCC. Authors’ conclusions Dermoscopy may be a valuable tool for the diagnosis of BCC as an adjunct to visual inspection of a suspicious skin lesion following a thorough history-taking including assessment of risk factors for keratinocyte cancer. The evidence primarily comes from secondary care (referred) populations and populations with pigmented lesions or mixed lesion types. There is no clear evidence supporting the use of currently available formal algorithms to assist dermoscopy diagnosis.